Using Fan Passion to Investigate Constraints to Student Attendance at College Football Games - Jason M. Simmons; Nels K. Popp; Chad D. McEvoy; Steven M. Howell (University of Kansas Libraries, 2018)
Given the decline in average student attendance at college football games nationwide, it is important for marketers to understand the constraints inhibiting student attendance. The current study addresses this issue by testing for differences in constraints affecting student nonattendance decisions based on their passion for the home team. Data were collected from students not attending games on six college campuses during actual football games. A total of 33 potential constraints to attendance were assessed. Results indicated statistically significant differences among intrapersonal, event-specific, and marketing-related constraints. Regardless of passion level, prior commitments to school and work were among the most highly-rated constraints to attendance. For highly-passionate fans, beverage costs, poor team performance, and watching the game on television were also highly-rated constraints. Low-passion fans, however, were constrained by time commitment necessary to attend, as well as lack of interest in football.